SENSITIVITY OF PEOPLE WITH DISABILITIES: A PERSPECTIVE FROM COMMUNICATION AND RELATIONSHIP THEORY A SYSTEMATIC LITERATURE REVIEW - Riyadi, Sabar; Subardhini, Meiti (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This research explores sensitivity in social interactions and communication with individuals with disabilities, using a systematic literature review approach. The aim was to understand how sensitivity is applied and understood in the context of disability, as well as the impact of a lack of sensitivity on the quality of life and social participation of individuals with disabilities. Findings from the literature review suggest that high sensitivity to the needs of individuals with disabilities correlates with greater feelings of inclusion and better-quality interpersonal relationships. Factors such as education and awareness, personal experience, social support, and community attitudes play an important role in shaping the level of sensitivity. Lack of sensitivity can lead to social isolation, reinforce stigma and discrimination, and negatively impact the psychological well-being and accessibility of individuals with disabilities. This research contributes to the development of a more inclusive theory of communication and provides practical recommendations for improving sensitivity in social interactions. Practical implications include developing education and training programs, increasing social support, implementing inclusive policies, creating a supportive environment, and promoting public awareness. Further research is needed to deepen understanding of the factors that influence sensitivity and test the effectiveness of interventions designed to increase sensitivity towards individuals with disabilities.